Emerging trends in sustainable food processing industry - Abdul Manap, Mohd Yazid; Yusof, Yus Aniza (IOP Publishing, 2021)
Food industry undergoes a dynamic innovation and digital transformation in ensuring food security and sustainability in the rapidly growing global population. In this sense, it is necessary to evaluate the technological trends and advances that will change the food processing industry. It is crucial to evaluate the influence of food processing technology to produce a nutritious and easy-to-handle food as well as its supply chain. This is particularly important to meet certain standards and customers' demands, and this paper presents halal requirements in the supply chain. Digital technology can also help the food industry in the new era to make it easier for consumers to get food more easily, quickly, and with more options without having to go to the food premises. Therefore, this paper discusses on thermal and non-thermal food processing trends in the context of preparation of ready-to-eat food, three-dimensional (3D) food printing, and utilisation of digital technology in food industry and services.